Antitrust Treatment of Bundled Discounts and Rebates in the United States and Europe: Mapping Uncharted Territories - Hui Hua (UCL Journal of Law and Jurisprudence, 2015)
Bundled discounting is one of the most unsettled areas of competition law. The economic and legal thinking behind this particular type of unilateral practices is in a constant state of flux. Advances in economics have illustrated a strong theoretical case that, even though such practice generally does not raise antitrust concerns, bundled discounting by a monopolist may nonetheless harm competition in some circumstances. What troubles law makers and enforcement authorities, is how best to categorise, prevent, detect, control and regulate such harm. This article attempts to clarify as well as organise coherently some of the important components of the main arguments presented by antitrust experts in this area. It surveys the recently proposed antitrust liability standards on how to distinguish procompetitive and anticompetitive bundling practices, and explores whether appropriate liability standards for analysing bundled discounts by dominant players are now more discernible. Read more